Pengaruh Promosi dan Harga Terhadap Keputusan Pembelian Konsumen Produk Perawatan Kulit Merek Skintific di Jakarta Barat: The Effect of Promotion and Price on Consumer Purchasing Decisions for Skintific Skin Care Products in West Jakarta - Tri Mulya Wati; Darkiman Ruminta; Dudi Duta Akbar (CV Warnak Johanna Nusantara, 2025)
This research has a background problem that is the promotion and price of Skintific brand products to consumers in West Jakarta. This skincare trend is increasing along with modern lifestyles and the influence of social media. Skintific has become a popular brand due to its aggressive marketing strategy, especially on TikTok. Although known as a premium quality product, Skintific's price is considered not commensurate with its quality when compared to local brands. The